UPAYA MENINGKATKAN HASIL BELAJAR SISWA MENGENAI REDOKS DAN SEL ELEKTROKIMIA DENGAN MENGGUNAKAN PENDEKATAN PEMBELAJARAN STEM (SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATICS): Penelitian Tindakan Kelas pada Pembelajaran Kimia di Kelas 12 MIPA-2 SMAN 1 Cikatomas - Mulyadi, Wahyu (LPPM Universitas Bina Bangsa, 2023)
The reality in the field that chemistry learning in Grade 12 MIPA-2 SMA Negeri 1 Cikatomas has not been solved. Students' difficulties in understanding chemistry learning are: 1) problem submission, 2) implementation of experiments for observation, and 3) conclusion making. This is evidenced by the achievement of chemistry learning results about Redox and Electrochemical Cells so far is still low. The average score of Class 12 MIPA-2 previously only reached 74. The test results are still low when compared to the minimum completeness criterion, which is 77. Based on the fact that in Grade 12 MIPA-2 SMA Negeri 1 Cikatomas student learning outcomes are still low, an effort is needed to improve student learning outcomes. One alternative method to help improve learning outcomes is to use the STEM (Science, Technology, Engineering, and Mathematics) Learning Approach. The purpose of Classroom Action Research (PTK) is to find out and improve chemistry lessons about Redox and Electrochemical Cells using the STEM (Science, Technology, Engineering, and Mathematics) Learning Approach in Grade 12 MIPA-2 SMA Negeri 1 Cikatomas. The method used in this study is Classroom Action Research (PTK), which is a form of action research that is directly carried out in the classroom. Based on the results of the study that: Learning implementation plan through the application of STEM (Science, Technology, Engineering, and Mathematics) Learning Approach to increase student understanding in Redox and Electrochemical Cell learning in Grade 12 MIPA-2 SMA Negeri 1 Cikatomas, in cycle I by 77.5% and cycle II by 90%. The process of implementing learning through the application of the STEM (Science, Technology, Engineering, and Mathematics) Learning Approach to increase student understanding in Redox and Electrochemical Cell learning in Grade 12 MIPA-2 SMA Negeri 1 Cikatomas, in teacher activities in cycle I by 75%, in cycle II increased to 83.3%. In the first cycle student activities it was 70.8% and in the second cycle it increased to 81.3%. Student learning outcomes in learning Redox and Redox Electrochemical Cells and Electrochemical Cells in Grade 12 MIPA-2 SMA Negeri 1 Cikatomas through the application of the STEM (Science, Technology, Engineering, and Mathematics) Learning Approach have improved with very good criteria. This can be proven by student learning outcomes in cycle I of 76 while in cycle II increased by 82